Prototyping a scalable smart village to simultaneously create sustainable development and enterprise growth opportunities - Darwin, Solomon, (SAGE Knowledge. Cases., 2017)
This case focuses on the development of a Smart Village in the village of Mori, in the state of Andhra Pradesh, India. The Chief Minister of the state, N. Chandrababu Naidu, has recently completed a series of visits to rural villages in his state of 60 million residents, 35 million of whom live in rural areas. Minister Naidu seeks to create a new policy mechanism to address the many unmet needs of his constituents in Andhra Pradesh. He has decided to launch an experiment called Smart Villages.The case describes the many unmet needs of rural villagers in India, and also discusses some of the approaches that the Chief Minister had tried in an earlier period, before his party lost power. Back in office as Chief Minister, he is now motivated to try something new.